2019
DOI: 10.1021/acssuschemeng.9b03154
|View full text |Cite
|
Sign up to set email alerts
|

Succinimide-Based Ionic Liquids: An Efficient and Versatile Platform for Transformation of CO2 into Quinazoline-2,4(1H,3H)-diones under Mild and Solvent-Free Conditions

Abstract: Multifunctional succinimide-based ionic liquids (SIILs) were well-designed and synthesized, and they were used as a dual solvent–catalyst for efficient transformation of CO2 and 2-aminobenzonitriles into quinazoline-2,4­(1H,3H)-diones under mild conditions. The catalytic behaviors, including the effects of anion–cation structures and reaction parameters, catalyst recyclability, and versatility were thoroughly studied. The optimum [HTMG]­[Suc] comprising a tetramethylguanidine cation and a succinimide anion sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…By 1 H NMR analysis, two obvious changes for the proton signal of amino in 2-aminobenzonitrile appeared after interacting with [HTMG][Triz] (Figure 4). On the one hand, the proton signal (H-e) became broader and had a clear downfield shift from δ = 6.000 to 6.035 ppm; it might be because of the activation of the amino group by forming hydrogen bonds with the [HTMG] + cation, and the result was consistent with some other reported catalysts; 11,20,40 on the other hand, there appeared a new proton signal at δ = 6.903 ppm, which possibly be resulted from the strong interaction between the proton (H-f) with the [Triz] − anion. 20 Clearly, the changes indicated that both the cation and anion of the [HTMG][Triz] could weaken the N−H bond in the NH 2 group to activate the 2-aminobenzonitrile effectively.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…By 1 H NMR analysis, two obvious changes for the proton signal of amino in 2-aminobenzonitrile appeared after interacting with [HTMG][Triz] (Figure 4). On the one hand, the proton signal (H-e) became broader and had a clear downfield shift from δ = 6.000 to 6.035 ppm; it might be because of the activation of the amino group by forming hydrogen bonds with the [HTMG] + cation, and the result was consistent with some other reported catalysts; 11,20,40 on the other hand, there appeared a new proton signal at δ = 6.903 ppm, which possibly be resulted from the strong interaction between the proton (H-f) with the [Triz] − anion. 20 Clearly, the changes indicated that both the cation and anion of the [HTMG][Triz] could weaken the N−H bond in the NH 2 group to activate the 2-aminobenzonitrile effectively.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…The cyclization of 2-amino­benzonitriles with CO 2 is an atom-economical route to accessing quinazoline-2,4­(1 H ,3 H )-diones, which generally requires metal catalysts and high temperature and pressure. Basic ILs with anions such as acetate, azolate, , phenolate, and the succinimide anion were found to be capable of catalyzing this reaction due to the cooperative effects of cations and anions (Scheme A). We designed protic ILs based on the neutralization reaction of superbases (e.g., 1,8-diaza­bicyclo[5.4.0]­undec-7-ene, DBU) with trifluoroethanol (TFE), which could capture CO 2 with equimolar uptake via forming anionic carbonate, [TFECOO] − , under ambient conditions .…”
Section: Ionic-liquid-catalyzed Strategies For the Transformation Of ...mentioning
confidence: 99%
“…These puzzling phenomena encourage us to perform a detailed density functional theory (DFT) study, from which we expect to reveal (i) whether the mechanism proposed by Liu et al is applicable for understanding the high catalytic activity of [HDBU + ]­[TFE – ] with regards to the synthesis of quinazoline-2,4-(1 H ,3 H )-diones from 2-aminobenzonitriles reacting with CO 2 , (ii) if not, what the alternative molecular mechanism should be, (iii) what the nature of these puzzling phenomena shown in Table is. Our DFT calculations are expected to present a clear picture of how the protic ILs catalyze the titled reaction and to provide useful guidance for preparing quinazoline-2,4-(1 H ,3 H )-diones from the reactions of 2-aminobenzonitriles with CO 2 reasonably. , …”
Section: Introductionmentioning
confidence: 99%